(untitled) (LEARNing Landscapes, 2018)
Education for citizenship is more important than ever. The author describes a technology-supported curriculum that engages young teens in electronic discourse with peers on significant personal and societal issues and assists them in decision making on topics ranging from their personal futures to the futures of their communities, nation, and world. A further purpose is to use discourse as a bridge in developing the individual argumentive writing that students of all ages find so challenging.